2015
DOI: 10.1002/chem.201503132
|View full text |Cite
|
Sign up to set email alerts
|

New Fluorescence Domain “Excited Multimer” Formed upon Photoexcitation of Continuously Stacked Diaroylmethanatoboron Difluoride Molecules with Fused π‐Orbitals in Crystals

Abstract: The crystal-packing structures of seven derivatives of diaroylmethanatoboron difluoride (1 a-gBF2 ) are characterized by no overlap of the π-conjugated main units of two adjacent molecules (type I), overlap of the benzene ring π-orbitals of two adjacent molecules (type II), and overlap of the benzene and dihydrodioxaborinine rings π-orbitals of adjacent molecules (type III). The crystal-packing structures govern the fluorescence (FL) properties in the crystalline states. The FL domain that is present in type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 52 publications
2
59
0
Order By: Relevance
“…NMR spectra ( 1 H, 13 C, 19 F) were recorded at room temperature on a BRUKER AC 250 operating at 250 and 235 MHz for 1 H and 19 F, respectively. Data are listed in parts per million (ppm) and are reported relative to tetramethylsilane ( 1 H and 13 C); residual solvent peaks of the deuterated solvents were used as an internal standard.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…NMR spectra ( 1 H, 13 C, 19 F) were recorded at room temperature on a BRUKER AC 250 operating at 250 and 235 MHz for 1 H and 19 F, respectively. Data are listed in parts per million (ppm) and are reported relative to tetramethylsilane ( 1 H and 13 C); residual solvent peaks of the deuterated solvents were used as an internal standard.…”
Section: Synthesismentioning
confidence: 99%
“…[3,12] A similar behavior has been reported to account for "excited multimer" fluorescence in stacks of diaroylmethanoboron difluoride molecules built on π-orbital overlap between benzene and dioxaborine rings. [13] Therefore, the solid-state optical signature of difluoroboron β-diketonate dyes is generally strongly sensitive to supramolecular packing. Especially, in the case of analogous dyes based on chalcone ligands, aggregation underpins the considerable spectral shift toward long wavelengths and an aggregation induced NIR emission (AI-NIR-E) phenomenon thus operates.…”
Section: Introductionmentioning
confidence: 99%
“…X‐ray crystallographic analysis was carried out on a single crystal of 1BF 2 . The results show that an arbitrarily chosen molecule of this substance, M 0 , has a planar geometry and possesses 14 neighbors, that is two sets of seven kinds of pairs, M 0 /M 1 , M 0 /M 2 , M 0 /M 3 , M 0 /M 4 , M 0 /M 5 , M 0 /M 6 , and M 0 /M 7 (Figure a. Molecules in the M 0 /M 1 pair appear to be π‐stacked between a benzene (B, Figure a) ring on one and the 1,2‐dihydro‐2,6‐dioxaborinine (D) ring of the other ( B‐on‐D overlap), with a face‐to‐face distance of 3.74 Å (Figure b). In addition, a short distance of 2.57 Å exists between an H atom in the 4‐iodophenyl group of M 0 and the F atom in M 2 .…”
Section: Figurementioning
confidence: 99%
“…In a previous study, we demonstrated that a relationship exists between the π‐stacking interactions in crystalline diaroylmethanatoboron difluorides and the S 1 →S 0 electronic transitions . When π‐stacking in the crystalline structures of these substances takes place through continuous B‐on‐D overlap, the S 1 →S 0 electronic transition is forbidden and an “excited multimer” is generated by photoexcitation.…”
Section: Figurementioning
confidence: 99%
“…Notably, replacement of the F atoms in 1 BF 2 by phenyl groups causes near total loss of emission in solution . Moreover, when an electron‐donating alkyl group is incorporated at the 4‐position of the phenyl group of 1 BF 2 , the FL quantum yield increases …”
Section: Introductionmentioning
confidence: 99%